PENANGANAN DISMENORE PADA REMAJA PUTRI DI MADRASAH ALIYAH NEGERI MOJOSARI KABUPATEN MOJOKERTO - Wahyuningrum, Tria; Safirah, (JURNAL KEPERAWATAN BINA SEHAT, 2015)
Dysmenorrhea is a menstrual disorder that is often experienced by teenage girls is characterized by lower abdominal pain radiating to the waist and thighs. Many treatment of dysmenorrhea can be done by young women to reduce the pain that is felt. The aim of this study was to determine the treatment of dysmenorrhea in adolescent girls senior high school islamic in Mojokerto regency. This research is a quantitative study with descriptive design . The population around the teenage daughter of a class X , XI , and XII MAN Mojosari ever experienced dysmenorrhea 212 young women to obtain a sample of 138 adolescent girls taken with proportionate stratified random sampling. Methods of data collection using the questionnaire. The research result shows that the majority of young women dysmenorrhea deal with distraction techniques as much as 75 girls ( 54.34 % ) , nearly half of respondents, 44 girls ( 31.88 % ) deal with drug store , and 7 ( 14.47 % ) young women with dysmenorrhea handle less precise way that drinking fizzy drinks. Handling the distraction technique is done by focusing attention to divert pain. Recommended for young women to make the most effective treatment for dysmenorrhea pain level for example with seminars or consultationsKey Word : The handling of Dysmenorrhea, teenage girls